(3GdJbQjQGJs - (3GdcdHGSj GdfLaj, eMeO EHQGgje Hf MSjf GdcdHGSj GdfLaj, hdO SfI (B1322(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3hGdeQGO efg Gdecda gh fUhU (B... (3dG jNai Cf GdhGbYI GdJj jHJdi HgG Gdecda CeG Cf Jchf ef bHjd GdTHgGJ GdMcejI hCeG Cf Jchf ef bHjds
(3BNQgG (B:s
(3BNQgG(B: (3GdPj gh JhCe eY GdJLQj (B.. .. (3dCfg dh bWY HCf GdOYGA QDjI GdgdGd eSFdI hGLH aj GdhGbY dh bdfGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L (B4: 268s
(3GdPQjYI, L (B4: 268s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs